Teeth eruption disturbances: Two case reports - Čudović Borko; Schneider-Del Savio Trosten; Imhoff Vesna (Serbian Medical Society - Dental Section, Belgrade, 2009)
Teeth eruption disturbances are very important in everyday orthodontic praxis because those are the most common causes of the orofacial system deviations. The aim of this study was to show two clinical cases with teeth eruption failures and to explain possible causes and potential therapy. Two clinical cases of tooth ankylosis are described as well as complete plan and treatment procedure. Even the irregularities in tooth development were very complex, it was shown that in cases which go beyond the possibilities of bone remodelling, stable results, functional and aesthetic, may be achieved.